Galíciától az Isonzóig: Az első világháborús magyar líra - Lapis, József (Studia Litteraria, 2015)
In my essay, I intend to survey how the topic of the Great War influences the poetic material of the interwar period (with special respect to the duration of the war itself). First of all, it is obligatory to recall (and, in a way, rethink) the relevant works of such well-known authors like Endre Ady or Mihály Babits. The previous one is particularly important, because we can speak about innovative poetical (and not thematic) consequences in his case. I discuss more extensively the works of two minor poets of the era: the oeuvre of Géza Gyóni (the war poet of WWI Hungary) and Géza Juhász, whose expressive volume Háború (War) was published twenty years after its formation, only in 1937.